Tailoring of advanced poly(lactic acid)‐based materials: A review. Issue 12 (14th November 2021) - Milovanovic, Stoja; Pajnik, Jelena; Lukic, Ivana
Abstract: Poly(lactic acid) (PLA) stands out as the most promising biodegradable alternative to conventional petrochemical‐based polymers for manufacturing of high‐performance materials applied in medicine, pharmacy, food, textile, and electronic industry. This review was aimed to present the conventional and up‐to‐date technologies for PLA processing including melt blending and molding, hot melt extrusion, 3D printing, foaming, impregnation, thermally induced phase separation, nano‐ and microparticles preparation, wet and dry spinning processes. In addition, the effect of the processing parameters and polymer characteristics on the properties of the final material was elaborated. Diverse possibilities to tailor properties of PLA‐based materials by variation in polymer characteristics and concentration, solvent selection, drying method, processing pressure and temperature, incorporation of bioactive components, and so on were highlighted. The examples of the relations between processing methods, parameters, and end‐product properties are given for a better understanding of all aspects that need to be perceived for fabrication of PLA‐based materials with required performances. Abstract :